1996
DOI: 10.1902/jop.1996.67.5.486
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Chlorhexidine, Cetylpyridinium Chloride, Triclosan, and C31G Mouthrinse Products for Plaque Inhibition

Abstract: There are a large number of mouthrinse products available to the general public for use as adjuncts to oral hygiene. Many have not been evaluated and relatively few comparisons of products have been made. This study compared 4 mouthrinse products containing cetylpyridinium chloride (CPC), chlorhexidine, C31G, or triclosan with saline rinse included as a placebo control. Twenty dentate volunteers took part in this 4-day plaque regrowth study which had a single blind, randomized cross-over design balanced for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
1
4

Year Published

2003
2003
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(51 citation statements)
references
References 13 publications
2
43
1
4
Order By: Relevance
“…For instance, Renton-Harper et al (23) observed that formulas containing chlorhexidine presented greater antimicrobial activity than cetylpyridinium chloride and triclosan, as well as Monfrin and Ribeiro (14), whose experiments indicated that products containing chlorhexidine were more effective in reducing microbial populations in the saliva of volunteers, whereas products containing triclosan led to small decreases, and those containing essential oils did not reduce microbial populations.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Renton-Harper et al (23) observed that formulas containing chlorhexidine presented greater antimicrobial activity than cetylpyridinium chloride and triclosan, as well as Monfrin and Ribeiro (14), whose experiments indicated that products containing chlorhexidine were more effective in reducing microbial populations in the saliva of volunteers, whereas products containing triclosan led to small decreases, and those containing essential oils did not reduce microbial populations.…”
Section: Resultsmentioning
confidence: 99%
“…Representative standard formulations of oral rinses are supplemented with chlorhexidine digluconate, ethanol, essential oils, and detergents [7, 8]. Oral rinses can contain anti-inflammatory glucocorticoids and aloe vera, anesthetics such as lidocaine and morphine, antifungal nystatin, antihistamine diphenhydramine, and antimicrobials [911].…”
Section: Introductionmentioning
confidence: 99%
“…Although there are many products used to control plaque and gingivitis, chlorhexidine digluconate (CHX) has received the greatest attention due to its superior clinical and microbiological effectiveness [5][6][7][8]. It is considered as the gold standard for oral antiseptics [9].…”
Section: Introductionmentioning
confidence: 99%